The CHRNA3 rs578776 Variant is Associated with an Intrinsic Reward Sensitivity Deficit in Smokers - Robinson, Jason D.; Versace, Francesco; Lam, Cho Y.; Minnix, Jennifer A.; Engelmann, Jeffrey M.; Cui, Yong; Karam-Hage, Maher; Shete, Sanjay S.; Tomlinson, Gail E.; Chen, Tina T.; Wetter, David W.; Green, Charles E.; et al. (Frontiers in Psychiatry, 2013)
A compromised brain reward system has been postulated as a key feature of drug dependence. We examined whether several polymorphisms of genes found to regulate nicotinic acetylcholine receptor (nAChR) and dopamine (DA) expression were related to an intrinsic reward sensitivity (IRS) deficit we previously identified among a subgroup of smokers using event-related potentials (ERPs). We examined genetic polymorphisms within the CHRNA5-A3-B4 gene cluster (CHRNA3 rs578776, CHRNA5 rs16969968, LOC123688 rs8034191, and CHRNA3 rs1051730), the ANKK1 gene (rs1800497), and the D2 receptor gene (DRD2 rs1079597, DRD2 rs1799732) from 104 smokers of European ancestry in a smoking cessation trial. Prior to treatment, we recorded ERPs evoked by emotional (both pleasant and unpleasant), neutral, and cigarette-related pictures. Smokers were assigned to two groups (IRS+/IRS-) based on the amplitude of the late positive potential (LPP) component to the pictures, a neural marker of motivational salience. Smokers (n = 42) with blunted brain responses to intrinsically rewarding (pleasant) pictures and enhanced responses to cigarette pictures were assigned to the IRS- group, while smokers (n = 62) with the opposite pattern of LPP responding were assigned to the IRS+ group. Carriers of the protective minor T allele (T/T, C/T) of the CHRNA3 rs578776 were less likely to be members of the IRS- group than those homozygous for the at-risk C allele (C/C). The CHRNA3 rs578776 polymorphism did not differ on questionnaires of nicotine dependence, depressed mood, or trait affective disposition and did not predict abstinence at 6 months after the quit date. These results suggest that polymorphisms of genes influencing nAChR expression are related to an endophenotype of reward sensitivity in smokers.